Factors Associated with Death Anxiety in Elderly Batak Tribe who Live in Bandung - Mamat Lukman; Ferdinan Sihombing; Lia Meilianingsih (Jurnal Keperawatan Padjadjaran, 2018)
Death is something definite. Awareness about the certainty of the coming death raises different responses depending on each person, including the elderly. Differences in social background, beliefs, and life experiences have shaped their respective levels of spirituality elderly, but the elderly still be experiencing anxiety to face the death. Not infrequently the death anxiety felt excessively, causing symptoms that can be observed.This study aimed to analyze the factors associated with death anxiety in elderly Batak tribe who live in Bandung, which includes the quality of life, life satisfaction, and culture. The study employed a descriptive correlational design, particularly cross-sectional design. There were 98 elderly who served as participants. The samples were chosen by using accidental sampling methods and criteria for inclusion. The data were analyzed by using Chi-square and binary logistic regression.The results showed that there was correlation between life satisfaction, and culture with death anxiety in elderly Batak tribe who live in Bandung (the two of factors has p value < 0.001 each) and with the binary logistic regression analysis of the factors known that the satisfaction of life is the most dominant factor that associated with death anxiety with OR value of 0.122. Community nurses need to pay attention to the improvement of satisfaction of life of the elderly.The conclusion this research is High satisfaction of life of elderly people have an impact on reducing the risk of death anxiety in elderly people, without forgetting other factors.